2014
DOI: 10.3892/mmr.2014.2389
|View full text |Cite
|
Sign up to set email alerts
|

(−)-Epigallocatechin gallate selectively inhibits adenosine diphosphate-stimulated human platelet activation: Suppression of heat shock protein 27 phosphorylation via p38 mitogen-activated protein kinase

Abstract: Abstract. (-)-Epigallocatechin gallate (EGCG) is a major component of green tea. It has been demonstrated that EGCGhas an antithrombotic effect by inhibiting platelet aggregation. However, the detailed mechanisms underlying the effects of EGCG remain to be elucidated. The present study examined the effects of EGCG on human platelet activation by various stimulators and the exact underlying mechanisms. EGCG suppressed adenosine diphosphate (ADP)-stimulated platelet aggregation dose dependently between 30 and 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…It appears that the absorption of the less hydrophilic AcEGCG into the cells may be better than natural EGCG under the same conditions, resulting in increased bioavailability. This is consistent with the results of previous research . Moreover, compared with EGCG, AcEGCG demonstrated more effective protection from H 2 O 2‐ induced toxicity in human melanocytes.…”
Section: Discussionsupporting
confidence: 92%
“…It appears that the absorption of the less hydrophilic AcEGCG into the cells may be better than natural EGCG under the same conditions, resulting in increased bioavailability. This is consistent with the results of previous research . Moreover, compared with EGCG, AcEGCG demonstrated more effective protection from H 2 O 2‐ induced toxicity in human melanocytes.…”
Section: Discussionsupporting
confidence: 92%
“…A number of potential mechanisms were proposed to explain the anti-inflammatory effect of EGCG. For example, several studies indicated that EGCG downregulated the TLR4independent signal-elicited phosphorylation of MAPK and also downregulated AP-1 (41,42). Given the suppressing effect of EGCG on TLR4-independent inflammation stimuli, there may be several anti-inflammation mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to showing that green tea catechins were involved in inhibition of platelet aggregation, studies suggested that catechins may affect several cellular targets that are related to platelet activation, including: through the arachadonic acid pathway, inhibition of a cytoplasmic increase in calcium, decreased thrombaxane A 2 (TXA 2 ) production, and inhibition of cyclooxygenase-1 (COX)-1 [90][91][92][93]. A study using human platelets concluded that EGCG was able to inhibit platelet activation by adenosine diphosphate (ADP) stimulation, and suppressed the p38 MAPK phosphorylation of heat shock protein 27 (HSP27), which would inhibit the release of pro-thrombotic contents from platelets [94].…”
Section: Platelet Aggregationmentioning
confidence: 99%